2006
DOI: 10.1021/ja0560736
|View full text |Cite
|
Sign up to set email alerts
|

A Three-State Mechanism for DNA Hairpin Folding Characterized by Multiparameter Fluorescence Fluctuation Spectroscopy

Abstract: The folding of a dye-quencher labeled DNA hairpin molecule was investigated using fluorescence autocorrelation and cross-correlation spectroscopy (FCS) and photon counting histogram analysis (PCH). The autocorrelation and cross-correlation measurements revealed the flow and diffusion times of the DNA molecules through two spatially offset detection volumes, the relaxation time of the folding reaction, and the total concentration of DNA molecules participating in the reaction. The PCH measurements revealed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
195
3
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(218 citation statements)
references
References 44 publications
16
195
3
4
Order By: Relevance
“…[4,5] Although our hairpin data were consistent with a two-state model via the chi-squared metric, we also observed a systematic deviation between our data and the model. Recent studies of DNA hairpin dynamics have identified putative intermediates in the folding pathway, [36,37] which could explain this discrepancy. However, we caution that the detection of such intermediates by PDA should involve the use of novel experimental controls, and not simply an increase in the number of free parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4,5] Although our hairpin data were consistent with a two-state model via the chi-squared metric, we also observed a systematic deviation between our data and the model. Recent studies of DNA hairpin dynamics have identified putative intermediates in the folding pathway, [36,37] which could explain this discrepancy. However, we caution that the detection of such intermediates by PDA should involve the use of novel experimental controls, and not simply an increase in the number of free parameters.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to more complex kinetic schemes, as identified in recent biophysical studies of DNA hairpins. [36,37] While some of these behaviors are expected to occur on timescales too short to be detected by PDA (e.g. multiple loop orientations in the open conformation), longerlived states (e.g.…”
mentioning
confidence: 99%
“…The system is simple enough for exhaustive detailed studies yet sufficiently sophisticated to serve as a paradigm for more complex RNA folding kinetics. There have been extensive studies on DNA hairpin folding kinetics using laser temperature-jump (4,55) and fluorescence correlation spectroscopy (8,43,44,52) techniques. In contrast, there are only very limited experiments on RNA hairpin (and pseudoknot) folding kinetics (54,64,69,111,113,114).…”
Section: Hairpin and Pseudoknot Folding Kineticsmentioning
confidence: 99%
“…19 This hypothesis has been challenged by several recent studies that suggest a more complex pathway, involving intermediate states containing misfolded or partially folded configurations. [20][21][22] Additionally, there have been diverse, and sometimes contradictory, experimental observations and interpretations of hairpin formation kinetics. Fluorescence energy transfer and fluorescence correlation spectroscopy measurements 23 have reported an Arrhenius temperature dependency with a positive activation enthalpy for the hairpin closing rates.…”
Section: Introductionmentioning
confidence: 99%